A microscopic image stitching algorithm with improved energy function - WANG Jiang’an; LIANG Wenqian; HUANG Le; QIN Linzhen (Dianxin kexue)
Addressing the challenge of traditional optimal suture algorithms in effectively eradicating splicing seams after fusing microscopic images, an image fusion optimization algorithm based on the optimal suture was proposed. Firstly, ORB was used to extract features from the to-be-spliced images and locate the overlapping region. Secondly, an improved energy function was designed and combined with the dynamic planning technique to effectively search for the optimal suture line in the overlapping region. Based on this line, the improved fusion method was further used to fuse the two images. Finally, the Poisson fusion method was utilized to eliminate the splicing seams existing between the overlapped and non-overlapped regions to obtain the final image. The experimental results show that this method improves the similarity of the pixels on both sides of the optimal suture line by about 5%, reduces the energy loss, eliminates the splicing seam, and improves the image quality.